Propolis – quality analysis and use in topical formulations - Ramanauskiene Kristina; Inkeniene Asta Marija; Perminaite Kristina; Zilius Modestas; Majiene Daiva (Acta Pharmaceutica)
The aim of this study was to produce propolis extracts, assess their quality and effect on skin cells and determine the penetration of active ingredients from designed semi-solid topical formulations. The use of higher-concentration ethanol and a larger amount of raw material allows extracting a larger quantity of active ingredients from raw propolis. Ultrasound extraction is an effective method for the production of aqueous extracts of propolis. The results show that depending on concentration, propolis extracts reduce the viability of keratinocytes. The phenolic compounds under observation penetrated the epidermis and dermis from designed formulations. The base of semi-solid formulation influences the efficacy of propolis preparations. The overall quantity of phenolic compounds that penetrated the skin was around 2 % from the ointment and 1.5 % from the cream.